China in 2020 a new type of superpower - Hu, Angang (Washington, D.C. Brookings Institution Press, 2011)
"Explains how China, as the world's largest emerging market, will impact global economic growth, FDI flows, energy consumption, climate change, and other arenas, with a proposed strategic framework that would guide the country's rise while maximizing positive impacts and minimizing any negative externalities"--Provided by publisher.
China, an emerging superpower -- Economic development : past, present, and future -- Demographic challenges : an aging society and rapid urbanization -- A healthy China : progress and problems -- Education and human resources -- Science, technology, and innovation -- Climate change and sustainable growth -- Development goals and grand strategy.
Keywords: Health status indicators -- China; Environmental indicators -- China; Science indicators -- China; Technology indicators -- China; China -- Economic conditions -- 2000-.; China -- Social conditions -- 2000-.